2018
DOI: 10.1016/j.semcdb.2017.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Studying protein-DNA interactions using atomic force microscopy

Abstract: Atomic force microscopy (AFM) has made significant contributions to the study of protein-DNA interactions by making it possible to topographically image biological samples. A single protein-DNA binding reaction imaged by AFM can reveal protein binding specificity and affinity, protein-induced DNA bending, and protein binding stoichiometry. Changes in DNA structure, complex conformation, and cooperativity, can also be analyzed. In this review we highlight some important examples in the literature and discuss th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 146 publications
(154 reference statements)
2
31
0
Order By: Relevance
“…Furthermore, at higher XPA concentrations, a second band of higher molecular weight appeared, indicating binding of an additional XPA protein. It is important to note that any affinity of XPA for DNA ends could obscure EMSA results in terms of (a) specificity, as end-binding (a common feature of DNA-binding proteins 38,39 ) would increase overall binding on both substrates, thereby lowering the apparent specificity for the lesion, and (b) stoichiometry, as separate XPA proteins bound to the lesion and the end of the DNA would migrate the same as a true dimer in the gel. If XPA has fairly high non-specific binding affinity, then embedding a lesion in a long stretch of non-damaged DNA might pose difficulties in damage recognition.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, at higher XPA concentrations, a second band of higher molecular weight appeared, indicating binding of an additional XPA protein. It is important to note that any affinity of XPA for DNA ends could obscure EMSA results in terms of (a) specificity, as end-binding (a common feature of DNA-binding proteins 38,39 ) would increase overall binding on both substrates, thereby lowering the apparent specificity for the lesion, and (b) stoichiometry, as separate XPA proteins bound to the lesion and the end of the DNA would migrate the same as a true dimer in the gel. If XPA has fairly high non-specific binding affinity, then embedding a lesion in a long stretch of non-damaged DNA might pose difficulties in damage recognition.…”
Section: Resultsmentioning
confidence: 99%
“…It allows for visualization of these molecules and its complexes deposited over a surface with nanometer resolution, preserving their native structure [44]. AFM has been utilized to characterize protein-protein and protein-DNA interactions and conformations; it also allows determining the specificity of proteins binding to specific sites on DNA [45,46]. Due to these features, AFM was used in this work to explore the changes occurring on the surface of the quartz crystal during DNA immobilization and hybridization processes.…”
Section: Real-time Quantitative Polymerase Chain Reactionmentioning
confidence: 99%
“…91,96 AFM studies with specific IHF-DNA complexes revealed single broad distributions peaked at bending angles of ~120-130°, with a range that covered bending angles from ~80° to ~160°. 27,33 These AFM studies were done with other IHF-DNA complexes; we are unaware of similar studies with IHF-H'. Notably, the range of bent conformations observed in AFM covers what we expect for the low-FRET state (with one site kinked) and for the high-FRET state (with both sites kinked).…”
Section: Discussionmentioning
confidence: 99%
“…and an LAS Award for Faculty in the Sciences from the University of Illinois at Chicago (to A.A.) This work was also supported by the Intramural Research Program of the National Institutes of Health (NIH, CIT). 33…”
Section: Acknowledgmentsmentioning
confidence: 99%
See 1 more Smart Citation